Ultrathin, Soft, Bioresorbable Organic Electrochemical Transistors for Transient Spatiotemporal Mapping of Brain Activity - Mengge Wu; Kuanming Yao; Ningge Huang; Hu Li; Jingkun Zhou; Rui Shi; Jiyu Li; Xingcan Huang; Jian Li; Huiling Jia; Zhan Gao; Tsz Hung Wong; et al. (Advanced Science)
Abstract A critical challenge lies in the development of the next‐generation neural interface, in mechanically tissue‐compatible fashion, that offer accurate, transient recording electrophysiological (EP) information and autonomous degradation after stable operation. Here, an ultrathin, lightweight, soft and multichannel neural interface is presented based on organic‐electrochemical‐transistor‐(OECT)‐based network, with capabilities of continuous high‐fidelity mapping of neural signals and biosafety active degrading after performing functions. Such platform yields a high spatiotemporal resolution of 1.42 ms and 20 µm, with signal‐to‐noise ratio up to ≈37 dB. The implantable OECT arrays can well establish stable functional neural interfaces, designed as fully biodegradable electronic platforms in vivo. Demonstrated applications of such OECT implants include real‐time monitoring of electrical activities from the cortical surface of rats under various conditions (e.g., narcosis, epileptic seizure, and electric stimuli) and electrocorticography mapping from 100 channels. This technology offers general applicability in neural interfaces, with great potential utility in treatment/diagnosis of neurological disorders.